Xanthium strumarium extract inhibits mammalian cell proliferation through mitotic spindle disruption mediated by xanthatin. (24th December 2016) - Sánchez-Lamar, Angel; Piloto-Ferrer, Janet; Fiore, Mario; Stano, Pasquale; Cozzi, Renata; Tofani, Daniela; Cundari, Enrico; Francisco, Marbelis; Romero, Aylema; González, Maria L.; Degrassi, Francesca
Abstract: Ethnopharmacological relevance: Xanthium strumarium L. is a member of the Asteraceae family popularly used with multiple therapeutic purposes. Whole extracts of this plant have shown anti-mitotic activity in vitro suggesting that some components could induce mitotic arrest in proliferating cells. Aim of the sudy: Aim of the present work was to characterize the anti-mitotic properties of the X. strumarium whole extract and to isolate and purify active molecule(s). Materials and methods: The capacity of the whole extract to inhibit mitotic progression in mammalian cultured cells was investigated to identify its anti-mitotic activity. Isolation of active component(s) was performed using a bioassay-guided multistep separation procedure in which whole extract was submitted to a progressive process of fractionation and fractions were challenged for their anti-mitotic activity. Results: Our results show for the first time that X. strumarium whole extract inhibits assembly of the mitotic spindle and spindle-pole separation, thereby heavily affecting mitosis, impairing the metaphase to anaphase transition and inducing apoptosis. The purification procedure led to a fraction with an anti-mitotic activity comparable to that of the whole extract. Chemical analysis of this fraction showed that its major component was xanthatin. Conclusions: The present work shows a new activity of X. strumarium extract, i.e. the alteration of the mitotic apparatus in cultured cells that may be responsible for the anti-proliferative activity of the extract. Anti-mitotic activity is shown to be mainly exerted by xanthatin. Graphical abstract: